A comparative study of the hydrodynamic characteristics of permeable twin-flat-plate and twin-arc-plate breakwaters based on physical modeling. (1st January 2021) - Li, Xueyan; Wang, Lixue; Wang, Qing; Xie, Tian; You, Zaijin; Song, Kezhi; Xie, Xiaomin; Wan, Xiang; Hou, Chengyi; Wang, Yukun
Abstract: To explore the similarities and differences between permeable twin-flat-plate (TFP) and twin-arc-plate (TAP) breakwaters in terms of their wave attenuation performance and structural behavior, the two breakwaters are compared in terms of the wave transmission coefficient, reflection coefficient, wave pressure, wave force, and flow field characteristics by physical model tests. The results show the wave transmission coefficients of the TAP breakwater are 34.5% and 25% smaller than those of the TFP breakwater in the emerged state and at the still water level, respectively. The wave reflection coefficient of the TFP breakwater shows a maximum increase of approximately 66.7% compared with the TAP breakwater. Except for the upper surface of the upper plate in the emerged state, the wave pressures on the TAP breakwater are smaller than those on the TFP breakwater by up to 62.4%. The vertical wave forces on the TAP breakwater are less than those on the TFP breakwater by up to 40.2%. The characteristics of the flow field around the TFP and TAP breakwaters are markedly different. The results of this study provide necessary theoretical guidance for engineering applications of permeable plate-type breakwaters. Highlights: Twin-flat-plate (TFP) and twin-arc-plate (TAP) breakwaters are compared by physical experiments. Transmission coefficient of TAP breakwater is smaller than that of TFP breakwater by up to 34.5%. Wave pressure on TAP breakwater is less than that on TFP breakwater by up to 62.4%. Vertical wave force on TAP breakwater is smaller than that on TFP breakwater by up to 40.2%.